2019
DOI: 10.1111/ecc.13069
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life associated with different cancer treatments in Chinese breast cancer survivors in Taiwan

Abstract: We assessed the quality of life (QoL) associated with patient's characteristics and different cancer treatments among Chinese breast cancer survivors in Taiwan. A cross‐sectional survey was conducted in 2017 where 193 patients with hormone receptor‐positive/human epidermal growth factor receptor‐2‐negative metastatic breast cancer were recruited. Three QoL questionnaires were administered: European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ‐C30), its breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…Breast is a special symbol of women's beauty and every woman wants to be beautiful". Although the results were not statistically signi cant due to small sample size, it is consistent with previous ndings of original studies and systematic reviews with meta-analysis [30,33,31,[34][35][36].…”
Section: Eq-vas Scores and Utility Scoressupporting
confidence: 90%
“…Breast is a special symbol of women's beauty and every woman wants to be beautiful". Although the results were not statistically signi cant due to small sample size, it is consistent with previous ndings of original studies and systematic reviews with meta-analysis [30,33,31,[34][35][36].…”
Section: Eq-vas Scores and Utility Scoressupporting
confidence: 90%
“…One duplicate study was identified which reports the same patient sample (personal communication) and values, the most recent paper has been included in the analysis [ 19 , 20 ]. Five studies met the eligibility criteria [ 20 24 ]. A PRISMA flow diagram is shown in Fig 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, in Cheng et al, and's (2016) study, the patients' bodies and minds gradually recovered after initial treatment. The study has shown that breast cancer chemotherapy patients with higher symptom burden often had poorer quality of life (Ou et al, 2019). The quality of life is positively correlated with the survival time of cancer survivors (Hoerger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%